2016
DOI: 10.1016/j.jnoncrysol.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of Bi2O3-Nb2O5-TeO2 glasses

Abstract: Bi2O3-Nb2O5-TeO2 glasses show unusual annealing behavior with appearance of spherulites within the matrix glass structure for the Bi0.5Nb0.5Te3O8 composition. The textures resemble those found previously among polyamorphic Al2O3-Y2O3 glasses containing metastably co-existing high-and lowdensity phases produced during quenching. However the spherulites produced within the Bi2O3-Nb2O5-TeO2 glass are crystalline and can be identified as an "anti-glass" phase related to -Bi2Te4O11. We used high energy synchrotron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…This implies that with the addition of Ho 2 O 3 in the TTLG network, binodal decomposition might have occurred in GCs . Moreover, the elemental maps presented in Figure S‐II(b) and (c), Supporting Information, can not reveal the compositional fluctuation in the phase‐separated domains of Ho 2 O 3 ‐substituted GCs, which confirms that the event of phase separation for relevant samples is governed by density fluctuation only . Furthermore, density fluctuation‐driven phase separation leads to the controlled crystallization via binodal decomposition.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This implies that with the addition of Ho 2 O 3 in the TTLG network, binodal decomposition might have occurred in GCs . Moreover, the elemental maps presented in Figure S‐II(b) and (c), Supporting Information, can not reveal the compositional fluctuation in the phase‐separated domains of Ho 2 O 3 ‐substituted GCs, which confirms that the event of phase separation for relevant samples is governed by density fluctuation only . Furthermore, density fluctuation‐driven phase separation leads to the controlled crystallization via binodal decomposition.…”
Section: Discussionmentioning
confidence: 83%
“…The transparent GCs with the growth of nanostructured Bi 0.5 Nb 0.5 Te 3 O 8 (an analogous to the β ‐Bi 2 Te 4 O 11 fluorite‐type anti ‐glass phase) crystalline phase have been achieved owing to the controlled heat treatment of a 7.14Bi 2 O 3 −7.14Nb 2 O 5 −85.72TeO 2 glass system, which contains chains of corner linked TeO 3 and TeO 4 units with nonbridging oxygens (NBOs) coordinating NbO 6 and BiO 6 units . It could be understood that the presence of chains of corner linked TeO 3 and TeO 4 coordination polyhedral at an equal proportion and the presence of modifier cations surrounded by NBOs in the form of octahedral units lend the formation of tellurium‐rich anti ‐glass phase . Therefore, it is apparently clear that selecting more appropriate tellurium‐based glass composition and executing the controlled crystallization process support the development of nanostructured crystalline phases to obtain transparent GCs, which can further be utilized in nonlinear and NIR/mid‐IR (MIR) photonic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Although Pure TeO2 is known to be a poor glass former, glasses can be formed readily when small amounts of modifying components are added [18]. In a recent study the structure of glasses in the system Bi2O3-Nb2O5-TeO2, motivated in part by the similarity in the textures observed in some of these glasses with the apparent "polyamorphic" texture observed in yttrium aluminate systems [19].…”
Section: Tellurite Systemsmentioning
confidence: 99%
“…The database of glass short-range structural properties such as cation-oxygen bond lengths, co-ordination numbers and bond angle distributions is required for the fundamental understanding of glassy materials, making structure-property correlations, for the mathematical modeling of glass density, elastic moduli, linear and non-linear refractive indices, stress-optical properties and for machine learning. [21][22][23][24] Wilding et al 25 studied the structure of binary and ternary tellurite glasses within the system: Bi 2 O 3 -Nb 2 O 5 -TeO 2 by high energy X-ray diffraction. These studies revealed a glassy network consisting of interconnected TeO 4 and TeO 3 units correlated to the crystalline TeO 2 materials but possessing larger Te/Te separations due to the presence of TeO 3 groups and non-bridging oxygens (NBOs) that are linked to modier (Bi 3+ , and Nb 5+ ) cations.…”
Section: Introductionmentioning
confidence: 99%